ANALISIS BUKTI FORENSIK DIGITAL PENIPUAN TRANSAKSI ONLINE PADA LINE MESSENGER MENGGUNAKAN METODE FORENSIK LANGSUNG - Syamsul Arifin (2023)
The rapid development of computer technology is parallel to the increase in cybercrime. One example is the occurrence of fraud in online transactions. Such fraud can happen on the popular application called LINE Messenger, which is a multi-platform cloud-based instant messaging application that is free and non-profit. LINE is available for various operating systems such as Android, iOS, Windows Phone, Ubuntu Touch, and can also be accessed through computer devices like Windows, MacOS X, and Linux. Through the LINE application, users can exchange text messages, photos, videos, audios, documents, stickers, and various other file types. Every application running on a computer leaves behind traces of data and information in volatile memory, commonly known as Random Access Memory (RAM). Data and information stored in RAM can be obtained through a digital forensic technique known as "live forensics." Live forensics is an investigation method where the evidence collection process takes place while the perpetrator's computer or device is still actively in use. In the context of this research, the aim is to identify digital evidence related to cases of online transaction fraud found in volatile memory (RAM) and also on the disk of the machine. To achieve this goal, forensic tools called FTK Imager and WinHex are used. These tools are capable of retrieving and analyzing data and information stored in RAM. The results of this research consist of an analysis of digital evidence related to conversations, which can serve as significant evidence in uncovering cases of online transaction fraud.